Young Audiences, Theatre and the Cultural Conversation
XVII, 201 p. 48 illus.
Keywords: This volume offers rare insights into the connection between young audiences and the performing arts. Based on studies of adolescent and post-adolescent audiences, ages 14 to 25, the book examines to what extent they are part of our society’s cultural conversation. It studies how these young people read and understand theatrical performance. It looks at what the educational components in their theatre literacy are, and what they make of the whole social event of theatre. It studies their views on the relationship between what they themselves decide and what others decide for them. The book uses qualitative and quantitative data collected in a six-year study carried out in the three largest Australian States, thirteen major performing arts companies, including the Sydney Opera House, three state theatre companies and three funding organisations. The book’s perspectives are derived from world-wide literature and company practices and its significance and ramifications are international. The book is written to be engaging and accessible to theatre professionals and lay readers interested in theatre, as well as scholars and researchers.